PUBLIC ADMINISTRATION OF CULTURAL SPHERE IN RUSSIA: EXPERT VIEW - O. Kryshtanovskaya; A. Komarova; M. Zakharov (Вестник университета)
As a result of all-Russian expert survey the challenges of cultural management were discussed in order to reveal its weakest points. In the first place, according to the most experts, there is a problem of underfunding, which entails serious consequences such as personnel stagnation, increasing inequality of access to cultural heritage of various strata of the population and regions. In addition, commercialisation of culture lowers its overall level that negatively affects the state of society as a whole. Participants of the survey suggested a range of measures designed to improve the quality of public administration in cultural sector in both law and enforcement aspects. Most experts are convinced that new cultural law which would facilitate an overcoming dramatic inequality is needed.